(3TQM cJGH GdJUQjas - (3GdSYO GdJaJGRGfj , SYO GdOjf eSYhO Hf YeQ Hf YHO Gddg GdJaJGRGfj,J (B793 (3g` s
(3ChdgG (B:s
(3aGbhd deG cGf f GdhGLH Ydi WGdH cd TF Cf jJUhQ Pdc GdTF ChdkG djchf Ydi HUjQI ai WdHg EYde Cf GdJUQja gh JaYjd ef GdUQa ddeHGdZI ai GddZI s
(3BNQgG (B:s
(3hCeG ai ZjQg aGdfhY efg cGdeQI HdGaQb ai GddaX hGdeaGQb GdbQGFf GdNGQLjI hcPG GdHhGbi hGddg CYde s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B2s
(3JHUQI GdYfhGf (B:s
(3TQM s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B219 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B12 - (3U (B228 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B2 - (3U (B430s
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI LjOI s
Keywords: (3GddZIs